Oxidation of Aromatic Anils by Sodium Perborate in Aqueous Acetic Acid Medium - Venkatesh, R.; Karunakaran, K. (Asian Journal of Chemistry, 2014)
The kinetics of oxidation of 9 meta- and 15 para- substituted aromatic anils by sodium perborate were investigated in aqueous acetic acid medium. The reaction was second order with respect to aromatic anil and first order with respect to the sodium perborate. The increase of [H+] in this oxidation retards the rate of the reaction. The observed rate constant for the substituents were plotted against the Hammett constant, s and a non-linear concave downward curve was obtained for the anils with substituents in the aniline moiety. The observed break in the log kobs versus s was attributed to the transition state whereas the non-linear concave upward curve was observed for the substituents in the benzaldehyde moiety and a non-linear concave upward curve was observed for the substituents in the combination of aniline and benzaldehyde moiety. The electron withdrawing substituents fall on one side of the curve, having a negative r value and the electron releasing substituents fall on the other side, with a positive r value and a suitable mechanism was proposed.